Odpowiedź :
x + y = 35
0,6x - 1,2y = 3
6x + 6y = 210
3x - 6y = 15
9x = 225
x = 25
25 + y = 35
x = 25
x = 25
y = 10
0,6x - 1,2y = 3
6x + 6y = 210
3x - 6y = 15
9x = 225
x = 25
25 + y = 35
x = 25
x = 25
y = 10
x+y=35
0,6x-1,2y=3 [: 0,6
x+y=35
x-2y=5
x=5+2y
5+2y+y=35
3y=30
y=10
x=25
0,6x-1,2y=3 [: 0,6
x+y=35
x-2y=5
x=5+2y
5+2y+y=35
3y=30
y=10
x=25
a + b = 35
0,6 a - 1,2 b = 3
a = 35 - b
0,6 ( 35 - b ) - 1,2 b = 3
21 - 0,6 b - 1,2 b = 3
- 1,8 b = 3 - 21
- 1,8 b = -18
b = 10
a = 35 - 10 = 25
a = 25, b=10
0,6 a - 1,2 b = 3
a = 35 - b
0,6 ( 35 - b ) - 1,2 b = 3
21 - 0,6 b - 1,2 b = 3
- 1,8 b = 3 - 21
- 1,8 b = -18
b = 10
a = 35 - 10 = 25
a = 25, b=10